Accessibility to digital technology: Virtual barriers, real opportunities - Botelho, Fernando H. F. (Assistive technology, 2021)
The potential of digital technology to assist persons with disabilities has always been known. The capabilities of digital devices have been improving so impressively for so long, that the assumption that in parallel the same is happening with accessibility is common. Unfortunately, accessibility for persons with disabilities is neither certain nor constant, and in fact, a conscious and systemic effort is required to ensure that the potential of digital technologies for inclusion is realized. Digital accessibility is best understood as a chain of dependencies where training, hardware, software, content, and standards must work together harmoniously, and each of these elements must be understood as a dynamic process. For example, smartphones can be incompatible with hearing aids required by the deaf, touch screens too sensitive for those with motor impairments, and web pages often lack the text labels needed by screen reading software used by the blind. Even if each of these examples is fixed, the accessibility may be short lived if the production process behind that hardware or software was not corrected, as the digital world is constantly being updated. Training, hardware design, software development, content production, and standards definition processes, must be pursued taking accessibility and affordability into account.